Alternative Tourism with a Woman's Face: The Kichwa-Amazonian Community of Shiripuno - Rivadeneyra Grefa, Teodoro; Rivadeneyra Grefa, Rocío; Lehtilä, Kari (Whispers from below: Community-based tourism and (other) Ecuadorian initiatives for alternative economies: A closer look, 2026)
Community-based tourism in Shiripuno is a practice of resistance and sustainability led by Kichwa women. This model integrates traditional agriculture with tourism to ensure economic livelihoods and the preservation of cultural identities. Collective self-management and women’s leadership transform the region into a space of sovereignty, where traditional culture serves as a political response to exclusion and the challenges of the global labor market.